Development of Human Resource Management Structural Equation Model of the Automotive Parts Manufacturing Industry in Thailand - Nanthasudsawaeng, Kritchouw (Community and Social Development Journal, 2022)
This research aims to study the human resource management model influencing the operational efficiency of the automotive parts manufacturing industry in Thailand. It is quantitative research and the research tool used was a questionnaire. The sample groups were executives of 500 establishments. The results showed that the knowledge management was average at a high level followed by human resource management, operational efficiency, and organizational innovation. The correlation analysis found that human resource management had a close relationship with organizational innovation. Knowledge management and operational efficiency were high as per the results of the concordance analysis of the model. It was found that the factors directly influencing operational efficiency were human resource management, organizational innovation, and knowledge management. These factors are important tools that help increase operational efficiency and create sustainable competitive advantages for the automotive parts manufacturing industry in Thailand.